Inbreeding depression in polyploid species: a meta-analysis - Clo, Josselin; Kolář, Filip (Biology letters, 2022)
Whole-genome duplication is a common mutation in eukaryotes with far-reaching phenotypic effects, the resulting morphological and fitness consequences and how they affect the survival of polyploid lineages are intensively studied. Another important factor may also determine the probability of establishment and success of polyploid lineages: inbreeding depression. Inbreeding depression is expected to play an important role in the establishment of neopolyploid lineages, their capacity to colonize new environments, and in the simultaneous evolution of ploidy and other life-history traits such as self-fertilization. Both theoretically and empirically, there is no consensus on the consequences of polyploidy on inbreeding depression. In this meta-analysis, we investigated the effect of polyploidy on the evolution of inbreeding depression, by performing a meta-analysis within angiosperm species. The main results of our study are that the consequences of polyploidy on inbreeding depression are complex and depend on the time since polyploidization. We found that young polyploid lineages have a much lower amount of inbreeding depression than their diploid relatives and their established counterparts. Natural polyploid lineages are intermediate and have a higher amount of inbreeding depression than synthetic neopolyploids, and a smaller amount than diploids, suggesting that the negative effect of polyploidy on inbreeding depression decreases with time since polyploidization.
Keywords: Magnoliopsida; Diploidy; polyploidy; Inbreeding Depression; Polyploidy; fitness; genome doubling; diploidie; inbrední deprese; Inbreeding; inbreeding depression; polyploid establishment; inbreeding; polyploidie